2016
DOI: 10.1111/1471-3802.12358
|View full text |Cite
|
Sign up to set email alerts
|

VÍDEO GAME NA ESCOLA E NA CLÍNICA: AUXILIAR DA INCLUSÃO

Abstract: Palavras-chave: Vıdeo game, Intervenc ßão com vıdeo game, Inclusão.O vídeo game vem sendo utilizado para diversas finalidades como lazer, reabilitac ßão e educac ßão. Foram realizadas duas pesquisas para verificar o uso do vídeo game como estrat egia em terapia convencional de fisioterapia e como recurso pedag ogico em aulas de Educac ßão Física com crianc ßas com paralisia cerebral. A intervenc ßão terapêutica utilizou jogos do Nintendo Wii e X-Box 360°kinect e recursos da terapia convencional durante dez ses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…The video game contributes to the development and maintenance of cognitive function and physical therapy, as it improves health care if the child with improved motor performance through postural control and balance, agility of movement, and communicative skills. (20) Contradicting that electronic games can make children more sedentary, an intervention was performed using games with dance, which concluded that this attitude adopted in schools can encourage positive behaviors at home. (16) Therefore, children and adolescents in the digital age should be encouraged to promote healthy lifestyles using electronic games, associating the desire of playing with the need for physical activity.…”
Section: Novel Methods To Collect Meaningful Data From Adolescents For the Development Of Health Interventionsmentioning
confidence: 99%
“…The video game contributes to the development and maintenance of cognitive function and physical therapy, as it improves health care if the child with improved motor performance through postural control and balance, agility of movement, and communicative skills. (20) Contradicting that electronic games can make children more sedentary, an intervention was performed using games with dance, which concluded that this attitude adopted in schools can encourage positive behaviors at home. (16) Therefore, children and adolescents in the digital age should be encouraged to promote healthy lifestyles using electronic games, associating the desire of playing with the need for physical activity.…”
Section: Novel Methods To Collect Meaningful Data From Adolescents For the Development Of Health Interventionsmentioning
confidence: 99%